Safety and Efficacy of Glucomannan for Weight Loss in Overweight and Moderately Obese Adults. (30th December 2013) - Keithley, Joyce K.; Swanson, Barbara; Mikolaitis, Susan L.; DeMeo, Mark; Zeller, Janice M.; Fogg, Lou; Adamji, Jehan
Abstract : Background . Few safe and effective dietary supplements are available to promote weight loss. We evaluated the safety and efficacy of glucomannan, a water-soluble fiber supplement, for achieving weight loss in overweight and moderately obese individuals consuming self-selected diets. Methods . Participants were randomly assigned to take 1.33 grams of glucomannan or identically looking placebo capsules with 236.6 mL (8 ounces) of water one hour before breakfast, lunch, and dinner for 8 weeks. The primary efficacy outcome was change in body weight after 8 weeks. Other efficacy outcomes were changes in body composition, hunger/fullness, and lipid and glucose concentrations. Safety outcomes included gastrointestinal symptoms/tolerance and serum liver enzymes and creatinine levels. Results . A total of 53 participants (18–65 years of age; BMI 25–35 kg/m 2 ) were enrolled and randomized. The two groups did not differ with respect to baseline characteristics and compliance with the study supplement. At 8 weeks, there was no significant difference between the glucomannan and placebo groups in amount of weight loss (− . 40 ± . 06 and − . 43 ± . 07, resp.) or other efficacy outcomes or in any of the safety outcomes. Conclusions . Glucomannan supplements administered over 8 weeks were well tolerated but did not promote weight loss or significantly alter body composition, hunger/fullness, or lipid and glucose parameters. This trial is registered with NCT00613600 .